Signatures of unresolved binaries in stellar spectra: implications for spectral fitting - El-Badry, Kareem; Eilers, Anna-Christina (Monthly notices of the Royal Astronomical Society, 2018)
Abstract. The observable spectrum of an unresolved binary star system is a superposition of two single-star spectra. Even without a detectable velocity offset